Angka Nol Sebagai Konsep Revolusioner: Kontribusi Islam Dalam Perkembangan Matematika Modern: Zero as a Revolutionary Concept: The Islamic Contribution to the Advancement of Modern Mathematics - Ala' Annajib Asyatibi; Fabilla Nimas Wedhari Ungu; Thohiroh Afifah (Universitas Darussalam Gontor, 2023)
The evolution of modern science and technology has become the focal point of Islam's role and contribution. Numerous Muslim scholars have made substantial contributions to the development of modern mathematics, laying the foundation for revolutionary advancements in this field. In this research endeavor, the researcher employs a literature review methodology, with data analysis conducted through content analysis. The objectives of this study are as follows: 1) to provide readers with insights into Islam's contributions to the advancement of modern mathematics, and 2) to inspire readers to cultivate a passion for learning akin to that exhibited by Muslim scholars of that era. The findings of this research demonstrate that the discovery of zero by Al-Khwarizmi constituted a revolutionary concept across various exact sciences. This development serves as an enduring testament to the profound and lasting impact of Muslim scientists on the progress of science and technology in the modern era, particularly within the realm of modern mathematics.